Distribution of α7 Nicotinic Acetylcholine Receptor Subunit mRNA in the Developing Mouse - Broide, Ron S.; Winzer-Serhan, Ursula H.; Chen, Yling; Leslie, Frances M. (Frontiers in Neuroanatomy, 2019)
Homomeric α7 nicotinic acetylcholine receptors (nAChRs) are abundantly expressed in the central and peripheral nervous system (CNS and PNS, respectively), and spinal cord. In addition, expression and functional responses have been reported in non-neuronal tissue. In the nervous system, α7 nAChR subunit expression appears early during embryonic development and is often transiently upregulated, but little is known about their prenatal expression outside of the nervous system. For understanding potential short-term and long-term effects of gestational nicotine exposure, it is important to know the temporal and spatial expression of α7 nAChRs throughout the body. To that end, we studied the expression of α7 nAChR subunit mRNA using highly sensitive isotopic in situ hybridization in embryonic and neonatal whole-body mouse sections starting at gestational day 13. The results revealed expression of α7 mRNA as early as embryonic day 13 in the PNS, including dorsal root ganglia, parasympathetic and sympathetic ganglia, with the strongest expression in the superior cervical ganglion, and low to moderate levels were detected in brain and spinal cord, respectively, which rapidly increased in intensity with embryonic age. In addition, robust α7 mRNA expression was detected in the adrenal medulla, and low to moderate expression in selected peripheral tissues during embryonic development, potentially related to cells derived from the neural crest. Little or no mRNA expression was detected in thymus or spleen, sites of immune cell maturation. The results suggest that prenatal nicotine exposure could potentially affect the nervous system with limited effects in non-neural tissues.